О моделировании спектральных характеристик смешанного процесса вибраций - Божко, А.Е.; Корсун, В.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
The theory of forming a simulated vibration with the use of spectral functions and spectral moments of an additive medley of stochastic and polyharmonic vibrations is given.